2014
DOI: 10.5194/angeo-32-7-2014
|View full text |Cite
|
Sign up to set email alerts
|

Low-latitude scintillation occurrences around the equatorial anomaly crest over Indonesia

Abstract: Abstract. We investigated low-latitude ionospheric scintillation in Indonesia using two GPS receivers installed at Bandung (107.6 • E, 6.9 • S; magnetic latitude 17.5 • S) and Pontianak (109.3 • E, 0.02 • S; magnetic latitude 8.9 • S). This study aimed to characterise climatological and directional ionospheric scintillation occurrences, which are useful not only for the physics of ionospheric irregularities but also for practical use in GNSS (global navigation satellite system)-based navigation. We used the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 26 publications
8
57
0
Order By: Relevance
“…These latitudinal ranges in the Southeast Asia longitudinal sector correspond to the EIA crest region. Beniguel et al (2009) and Abadi et al (2014) have reported that strong scintillations were concentrated in EIA crest region. Since intensity of the amplitude scintillation is proportional to amplitude of the plasma density, the strong scintillations occur at the EIA crest region, where the plasma density is high.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These latitudinal ranges in the Southeast Asia longitudinal sector correspond to the EIA crest region. Beniguel et al (2009) and Abadi et al (2014) have reported that strong scintillations were concentrated in EIA crest region. Since intensity of the amplitude scintillation is proportional to amplitude of the plasma density, the strong scintillations occur at the EIA crest region, where the plasma density is high.…”
Section: Discussionmentioning
confidence: 97%
“…Scintillation due to multipath frequently occurs at elevation angles less than 30°. We have excluded scintillation due to multipath, by applying the method of Abadi et al (2014), who have successfully excluded multipath-affected scintillation using the standard deviation of code-carrier divergence (sigmaCCDiv) measure. The other GPS receiver was installed at Kototabang (0.2°S, 100.3°E; 9.9°S magnetic latitude).…”
Section: Methodsmentioning
confidence: 99%
“…Estimations show that it takes a few hours after sunrise to refill depleted flux tubes at altitudes greater than 700 km [Huang et al, 2013;Sidorova and Filippov, 2014]. There are many reports on scintillation and EPB measurements in the ionization anomaly crest regions around 15°magnetic latitudes [Immel et al, 2004;Lee et al, 2009;Candido et al, 2011;Abadi et al, 2014]. Only those EPBs that have grown to apex altitudes of 750 km and above over the dip equator can be observed at such latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The zonal space of 50 km was also reported from observations [ Kelley , ; Kudeki and Bhattacharyya , ; Hysell et al , , ; Rodrigues et al , ; and Kudeki et al , ]. Theoretically, the plasma bubble occurrence is high when the solar terminator is aligned with the geomagnetic field line [ Tsunoda , ], so that equinoxes are the active seasons for plasma bubbles [e.g., Otsuka et al , ; Yokoyama et al , ; Abadi et al , ]. The plasma density is extremely low inside the plasma bubble compared to that of outside, and the plasma boundary is very sharp.…”
Section: Introductionmentioning
confidence: 63%